A comprehensive approach to characterizing bioactive compounds from Haplanthodes tentaculatus (L.) R. B. Majumdar using HR-LCMS and MTT assay - Trivedi, Parth B.; Badole, Madhavi (Current Botany, 2024)
The bioactive compounds in Haplanthodes tentaculatus (L.) R. B. Majumdar has demonstrated significant potential in addressing conditions like cancer, diabetes, inflammation, and microbial infections. This study employs high-resolution liquid chromatography mass spectrometry and network analysis to investigate these chemicals. The methanolic extract revealed 92 identified compounds, many of which exhibited inhibitory effects on MDA-MB-231 breast cancer cell growth. Aclacinomycin N, Ganoderic acid Mb, Cucurbitacin E, and Hydroquinidine displayed notable inhibitory effects. The extract demonstrated an IC50 value of 61.41±0.692 μg, showcasing its effectiveness in impeding cancer cell development. While promising, further research is needed to unravel the specific molecular pathways involved. The identification and characterization of distinct chemicals in the extract offer potential leads for medication development. This work underscores H. tentaculatus as a vital source of bioactive substances with potent anticancer properties, emphasizing the need for continued exploration in advancing cancer therapies.